ELEKTR MAYDONIGA KIRITILGAN KVANT GARMONIK OSSILLATORI ASOSIY HOLATI ENERGIYASINI HISOBLASHNING TAQRIBIY METODLARI - Yavidov, B.; Ashirova, N.; Sultanova, M.; Rustamov, D. (SCIENCE and SOCIETY, 2018)
In the article a harmonic oscillator, placed in the electric field, is considered. Approximate methods of calculation of ground state’s energy of the harmonic oscillator are given. In particular, two methods of energy calculation are presented. The author gives recommendations on applying the methods.
Keywords: quantum harmonic oscillator; electric field; Schrödinger equation; perturbation theory; variation approach